Evaluation of Scleroderma Clinical Trials Consortium training recommendations on modified Rodnan skin score assessment in scleroderma - Low, Andrea H. L. (Int J Rheum Dis, 2019)
AIM: The modified Rodnan skin score (mRSS) is a validated outcome measure for skin thickness in systemic sclerosis (SSc). Training has been shown to reduce variability in the measurement of mRSS. Our objective was to assess the inter‐ and intra‐observer variability of mRSS scoring using the proposed recommendations for training by the Scleroderma Clinical Trials Consortium (SCTC) and World Scleroderma Foundation (WSF). METHOD: Fifty‐two trainees and eight adult SSc patients participated in the SSc skin scoring workshop that was conducted in two sessions by four teachers. Each session, attended by 26 trainees, had a teaching and evaluation phase. The teaching phase comprised of: (a) lecture on mRSS scoring; (b) video demonstration of mRSS scoring; and (c) live demonstration of mRSS on one SSc patient. In the evaluation phase, each trainee independently assessed the mRSS in four SSc patients. For intra‐observer reliability, 14 trainees re‐assessed the mRSS of two SSc patients whom they had previously examined. We computed the inter‐ and intra‐observer variability using a linear mixed model. RESULTS: For the evaluation phase, 34 (65.4%) trainees were within five units of the established teachers' score in 3 out of 4 patients. Overall, the whole group had acceptable inter‐observer variability (intra‐class correlation coefficient [ICC] = 0.71, mean = 8.64 and within‐patient standard deviation [SD] = 4.25). The intra‐observer ICC was 0.85 and within‐patient SD was 2.73. CONCLUSION: There was good inter‐observer and excellent intra‐observer reliability. This is the first study examining the training of assessors using the SCTC/WSF recommendations and our results support the importance of standardized training for skin scoring.